Inhibition of the human organic anion transporter 1 by the caffeine metabolite 1-methylxanthine - Rengelshausen, Jens; Lindenmaier, Heike; Cihlar, Tomas; Walter-Sack, Ingeborg; Haefeli, Walter E.; Weiß, Johanna (Biochemical and biophysical research communications, 2004)
Caffeine (1,3,7-trimethylxanthine) is daily and widely consumed in beverages and food and is mainly metabolized to 1,7-dimethylxanthine and 1-methylxanthine. Indirect clinical evidence suggests that 1-methylxanthine interacts with the organic anion transport system in the human kidney. In this study the effect of caffeine and its main metabolites on the human organic anion transporter 1 (hOAT1) was investigated using CHO cells overexpressing hOAT1. The uptake of 6-carboxyfluorescein into CHOhOAT cells was significantly inhibited by ⩾100μM of 1-methylxanthine. Five hundred micromolar 1-methylxanthine was equieffective to 100μM probenecid. In contrast, caffeine and 1,7-dimethylxanthine did not inhibit the transport of 6-carboxyfluorescein at concentrations up to 500μM. In conclusion, the caffeine metabolite 1-methylxanthine inhibits the transport activity of hOAT1 in vitro. The central involvement of hOAT1 in the renal excretion of numerous drugs suggests that this inhibition may alter the pharmacokinetics of a series of clinically important drugs in humans.